Creative Human Resource Management Strategies for Addressing Organizational Change - Suminta Simatupang (Fakultas Ilmu Pendidikan Universitas Pahlawan Tuanku Tambusai, 2025)
Organizational change is inevitable in a dynamic business environment characterized by technological advancements, market shifts, and increasingly complex customer demands. The success of these changes is highly dependent on the role of Human Resource Management (HRM). The study purpose was to explore the strategic role of HRM in navigating organizational change, focusing on five key aspects: identifying major challenges, developing effective adaptation strategies, optimizing employee engagement and skills, improving communication to reduce uncertainty, and balancing the needs of both the organization and its employees. Materials and methods: A mixed-method approach was employed, incorporating quantitative surveys and qualitative interviews. Data were collected from a purposive sample of employees, managers, and external stakeholders involved in organizational change. The surveys examined employee perceptions of HR strategies, while in-depth interviews with HR managers provided insight into the role of leadership in facilitating change. Data analysis included qualitative theme identification and quantitative statistical analysis, yielding a comprehensive understanding of how HR strategies impact employee adaptation to organizational shifts. Results: The results indicate that modern businesses are moving toward value-oriented models, integrating financial goals with social and environmental impacts. Companies are increasingly focusing on employee well-being, reflecting its direct influence on productivity and organizational sustainability. The study found that effective HR strategies, such as fostering transparent communication, offering continuous learning opportunities, and promoting employee participation in decision-making, are crucial for reducing resistance and enhancing adaptation to change. Conclusions: In conclusion, the research highlights the critical role of HRM in driving successful organizational change. Through systematic planning and employee engagement, HRM helps businesses navigate external pressures while promoting innovation, efficiency, and long-term sustainability. The study contributes to the growing understanding of how modern organizations balance financial performance with broader social and environmental responsibilities.